2022
DOI: 10.3390/ijms23052479
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence of the Melatonin Calmodulin Interaction: Effect on CaMKII Activity

Abstract: Melatonin (MEL) is a pleiotropic indolamine that reaches multiple intracellular targets. Among these, MEL binds to calmodulin (CaM) with high affinity. In presence of Ca2+, CaM binds to CaM-dependent kinase II (CaMKII). The Ca2+-CaM/CaMKII pathway regulates a myriad of brain functions in different cellular compartments. Evidence showing the regulation of this cellular pathway by MEL is scarce. Thus, our main objective was to study the interaction of MEL with CaM and its effects on CaMKII activity in two microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Ca 2+ /CaM activates CaMKII directly or activates CaMK-kinase (CaMKK), which in turn phosphorylates CaMKIV [57] [58] [59] [60] [61]. Recent evidence suggests that Ca 2+ -CaM-MEL increased the activity of CaMKII in some experimental conditions [62]. Compared to MEL, AMK has been reported to have a higher affinity for Ca2+-CaM [63].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ /CaM activates CaMKII directly or activates CaMK-kinase (CaMKK), which in turn phosphorylates CaMKIV [57] [58] [59] [60] [61]. Recent evidence suggests that Ca 2+ -CaM-MEL increased the activity of CaMKII in some experimental conditions [62]. Compared to MEL, AMK has been reported to have a higher affinity for Ca2+-CaM [63].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, MT1 and MT2 receptors are expressed in the clone of ONPs used in this study, and previously it was demonstrated that olfactory neurons express NMDA receptors [ 21 , 49 ]. On the other hand, mitochondria play a key role in proliferation and at mitochondrial level; melatonin maintains the membrane potential, ROS balance, and ATP synthesis, the intramitochondrial synthesis of melatonin, as well as the indolamine release in the cytosol and diffusion into the intracellular membranes where it can produce intracrine effects, especially in the binding to calmodulin and the activation of its protein targets such as CaMK II [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This preserved the integrity of the ovarian reserve and delayed ovarian aging; the actions of melatonin seem not to require the conventional transmembrane melatonin receptors but may have involved intracellular binding sites, e.g., quinone reductase-2, calmodulin or RZR/RORα nuclear binding, etc. [ 219 , 220 ].…”
Section: Delaying Infertility With Melatoninmentioning
confidence: 99%